Gagasan Pendidikan dalam Perspektif Priyayi dan Santri: Kajian Pemikiran Ki Hadjar Dewantara dan KH Ahmad Dahlan - Hidayat, Fahri Hidayat (Matan : Journal of Islam and Muslim Society, 2023)
This article aims to examine the comparison of typologies of Islamic education thought from the priyayi and santri perspectives. In this case, Ki Hadjar Dewantara was chosen as the representative of the priyayi and Kiai Haji Ahmad Dahlan as the representative of the santri. The basic assumption in this study is that the idea of education presented by priyayi and santri contains religious values, but differs in the expression of the movement. The method used in the study is library research with a history of thought approach. This article concludes that Ki Hadjar Dewantara's educational ideas are heavily influenced by Islamic religious values and are expressed in the form of values, while Kiai Haji Ahmad Dahlan's educational ideas are expressed in the form of values, spirit, goals, and symbols.